ANALISIS PRODUKTIVITAS USAHATANI TEMBAKAU DI KABUPATEN PAMEKASAN - Fauziyah, Elys; Hartoyo, Sri; Kusnadi, Nunung; Kuntjoro, Sri Utami (Jurnal Organisasi dan Manajemen, 2010)
The goals of this study are to analyze variables which determined production, risk production and technical inefficiency on Tobacco farming in Pamekasan. Frontier production function model with heteroskedastic error structure estimated by Maximum Likelihood estimation developed by Kumbhakar is adopted to analyze the goals. The results show that farmers allocate inputs under optimal condition. The Consequences are productivity and efficiency at low level.